2021
DOI: 10.3390/drones5030093
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned Aerial Vehicles for Magnetic Surveys: A Review on Platform Selection and Interference Suppression

Abstract: In the past two decades, unmanned aerial vehicles (UAVs) have been used in many scientific research fields for various applications. In particular, the use of UAVs for magnetic surveys has become a hot spot and is expected to be actively applied in the future. A considerable amount of literature has been published on the use of UAVs for magnetic surveys, however, how to choose the platform and reduce the interference of UAV to the collected data have not been discussed systematically. There are two primary aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 109 publications
0
15
0
Order By: Relevance
“…However, it is necessary to minimize the impact of the aircraft on magnetic sensors, as shown in work [19], [20]. In addition, as mentioned in [21], the drone has the disadvantage that it should lift the entire weight of the aircraft only with battery power, so the flight time cannot exceed 30 minutes. Furthermore, existing studies demonstrated exploration results on flat land.…”
Section: Uav Explorationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is necessary to minimize the impact of the aircraft on magnetic sensors, as shown in work [19], [20]. In addition, as mentioned in [21], the drone has the disadvantage that it should lift the entire weight of the aircraft only with battery power, so the flight time cannot exceed 30 minutes. Furthermore, existing studies demonstrated exploration results on flat land.…”
Section: Uav Explorationmentioning
confidence: 99%
“…To apply to magnetic exploration, due to the helium gas cost, once it is injected into the airship, it should cover a larger area than the drone to make it feasible. Also mentioned in [21], ''the unmanned airship, which can stay in the air for a long time, is suitable for carrying out medium-area magnetic surveys.'' Recently, low-power and high-performance MCUs have been emerging due to the development of SoC (System on Chip) technology.…”
Section: Limitation and Future Workmentioning
confidence: 99%
“…For example, RQ-170 Sentinel UAV was captured by Iranian forces due to the interference signal on December 4, 2011 [14]. The external interference faced by UAVs can be divided into suppressed interference and deceptive interference [15]. Suppressed interference suppresses the source information by sending high-power interference, which is simple in implementation and has become a widely applied interference method recently.…”
Section: Introductionmentioning
confidence: 99%
“…The past decade has seen a variety of applications conducted by unmanned aerial vehicles (UAVs) in many fields, e.g., archaeology, remote sensing, geological prospecting, and unexploded ordnance (UXO) detection [1]. Among these applications, the use of UAVs for magnetic surveys is a booming branch of research [2].…”
Section: Introductionmentioning
confidence: 99%